Antioxidant Activity of Palm Kernel Oil-Vitamin C Nanoemulsion Evaluated Using the DPPH Assay Method - Muslim Suardi; Yunita Amanda; Yan Hendrika (LPPM Universitas Abdurrab, 2026)
Palm kernel oil (PKO) is an oil obtained from palm seeds (Elaeis guineensis Jacq) contains natural antioxidants. Objectives: Purposes of the study were to formulate, determine the physical characteristics of PKO nanoemulsions, and evaluate antioxidant activity. Method: The nanoemulsion was prepared into five formulations, F1, F2, F3, and F4 contained PKO at concentrations of 2, 2.5, 3, and 3.5% of PKO, respectively. F1, F2, F3, and F4 were added with vitamin C at a concentration of 2,5%. F5 as a control contained 3.5% PKO without vitamin C. Physical evaluations included organoleptic, viscosity, pH, centrifugation, transmittance, droplet size, zeta potential, and freeze-thaw tests. Antioxidant activity was evaluated using the DPPH assay method. Results: All of the physical evaluations fulfilled the requirement of nanoemulsion formulation. Antioxidant activity (IC50 value) of F1, F2, F3, F4, and F5 was 2.98 ± 0.21; 2.25 ± 0.23; 1.29 ± 0.05; 1.17 ± 0.12; and 51.96 ± 37.19 ppm, respectively. It was indicated very strong antioxidant activity, while for F5 (PKO without vitamin C) has strong activity (IC50 of 51.9 ppm). Conclusions: It is concluded that the PKO can be used as a antioxidant. PKO-Vitamin C can be formulated as a stable nanoemulsion.